ISOLASI DAN PENENTUAN KONDISI KERJA OPTIMUM AMILASE PADA UMBUT KELAPA (Coccos nucifera L.) - Lila Karina Nuryanti; Winni Astuti; Rudi Kartika (PROSIDING SEMINAR KIMIA, 2018)
Amylase is an enzyme that can catalyze stach hydrlysis into its simplier molecule as glucose. Coconut’s buds (Coccos nucifera L.) have high enough of carbohydrate content which amylase could have existed. The research are to determine protein concentration, optimum catalyst function and specified activity of amylase in coconut’s buds (Coccos nucifera L.). Coconut’s buds (Coccos nucifera L.) are isolated by extraction method using phospate buffer solution 0,1 M pH 7. The determination of protein concentration are used Bradford method. The determination of optimum catalyst function are used dinitrosalicylate acid (DNS), optimum catalyst fuction which are determined include of optimum pH, optimum temperature and optimum substrate concentration. The determination of specified activity of amylase are tested in optimum condition. The result of research are obtained the protein content are 2,933 mg/mL. The specified activity which are obtained from coconut’s buds (Coccos nucifera L.) are 80,376 U/mg in pH 6, temperature 50 ºC and substrate concentration 6,5 mg/mL Keywords : amylase, coconut’s buds, dinitrosalicylate acid (DNS) and specified activity.